The Formation of Religious Character Through the BCCT (Beyond Center and Circle Time) Learning Model at TK Muslimat Baiturrohmah Batu - Nurma Rosyiana Wardhani; Faridi Faridi; Yusuf Yusuf (Intiqad: Jurnal Agama dan Pendidikan Islam, 2026)
This study aims to determine the application and implications of religious character formation through the BCCT (Beyond Center and Circle Time) learning model at Muslimat Baiturrohmah Kindergarten. This research method is qualitative with the type of field research. The data collection process uses observation, interviews, documentation. Data analysis uses interactive Miles and Huberman. The results of the study indicate that, in the application of religious character formation through the BCCT (Beyond Center and Circle Time) learning model, there needs to be religious learning activities in the imtaq center such as distinguishing good and bad deeds, sequencing prayer movements, and sequencing the pillars of Islam. Doing daily habits will also form religious characters such as praying, reciting the Koran, tidying up toys, daily prayers. The implications of religious character formation through the BCCT (Beyond Center and Circle Time) learning model are that children are accustomed to carrying out worship without coercion, carrying out prayers devoutly, children have good and polite behavior, maintain cleanliness, help friends and teachers.knowledge received according to their interests and talents, thus producing superior and quality graduates who have the integrity of harmony between faith and science and technology.